Adaptations in gastrointestinal physiology after sleeve gastrectomy and Roux-en-Y gastric bypass. (March 2021) - Steenackers, Nele; Vanuytsel, Tim; Augustijns, Patrick; Tack, Jan; Mertens, Ann; Lannoo, Matthias; Van der Schueren, Bart; Matthys, Christophe
Summary: Linked to the growing obesity epidemic, demand for bariatric and metabolic surgery has increased, the most common procedures being sleeve gastrectomy and Roux-en-Y gastric bypass. Originally, bariatric procedures were described as purely restrictive, malabsorptive, or combined restrictive–malabsorptive procedures limiting food intake, nutrient absorption, or both. Nowadays, anatomical alterations are known to affect gastrointestinal physiology, which in turn affects the digestion and absorption of nutrients and drugs. Therefore, understanding gastrointestinal physiology is crucial to prevent postoperative nutritional deficiencies and to optimise postoperative drug therapy. Preclinical and clinical research indicates that sleeve gastrectomy accelerates liquid and solid gastric emptying and small intestinal transit, and increases bile acid serum levels, whereas its effects on gastrointestinal acidity, gastric and pancreatic secretions, surface area, and colonic transit remain largely unknown. Roux-en-Y gastric bypass diminishes gastric acid secretion, accelerates liquid gastric emptying, and increases bile acid serum levels, but its effects on intestinal pH, solid gastric emptying, intestinal transit time, gastric enzyme secretions, and surface area remain largely unknown. In this Review, we summarise current knowledge of the effects of these two procedures on gastrointestinal physiology and assess the knowledge gaps.